Mappings and some decompositions of continuity on nearly Lindelöf spaces - Fawakhreh, A.J.; Kiliçman, A. (Springer Science and Business Media LLC, 2002)
A topological space (X, τ) is said to be nearly Lindelöf if every regularly open cover of (X, τ) has a countable subcover. In this paper we study the effect of mappings and some decompositions of continuity on nearly Lindelöf spaces. The main result is that a δ-continuous image of a nearly Lindelöf space is nearly Lindelöf.